2018
DOI: 10.4067/s0718-221x2018005041601
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of precipitated calcium carbonate fillers using carboxymethyl cellulose /polyaluminium chloride: preparation and its influence on mechanical and optical properties of paper

Abstract: Inorganic fillers are usually used in papermaking industry to reduce production costs and enhance paper optical properties. As an attempt to improve fillers application in papermaking, carboxymethyl cellulose (CMC) and poly aluminum chloride (PAC) were used to encapsulate precipitated calcium carbonate (PCC) filler and modify its surfaces. In the first step, the optimum conditions for filler treatment (i.e. pH, CMC and PAC contents) were obtained. Through the second step, different amounts of CMCencapsulated P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…As the modified filler add-on increased, the generally expected strength values did not decrease, but an increase in non-significant values was observed (Figure 4). As the reason for the increases, it is seen that the effect of starch internal adhesion was realized, and with the increase in MC dosage, calcite grains encapsulated with cPAM support increased the retention by mak-ing wet-end bonding to the fibers and also preserved the strength (Chen et al, 2020;Mousavipazhouh et al, 2018) In accordance with the general studies, the filler addition showed a significant decrease in values such as CMT and breaking length (Bajpai, 2018). Nevertheless, it is thought to be higher than the filler-free paper values, which is due to the internal bonding effect of starch.…”
Section: Mechanical Properties Of the Fluting Paperssupporting
confidence: 69%
See 1 more Smart Citation
“…As the modified filler add-on increased, the generally expected strength values did not decrease, but an increase in non-significant values was observed (Figure 4). As the reason for the increases, it is seen that the effect of starch internal adhesion was realized, and with the increase in MC dosage, calcite grains encapsulated with cPAM support increased the retention by mak-ing wet-end bonding to the fibers and also preserved the strength (Chen et al, 2020;Mousavipazhouh et al, 2018) In accordance with the general studies, the filler addition showed a significant decrease in values such as CMT and breaking length (Bajpai, 2018). Nevertheless, it is thought to be higher than the filler-free paper values, which is due to the internal bonding effect of starch.…”
Section: Mechanical Properties Of the Fluting Paperssupporting
confidence: 69%
“…4). As the reason for the increases, it is seen that the effect of starch internal adhesion was realized, and with the increase in MC dosage, calcite grains encapsulated with cPAM support increased the retention by making wet-end bonding to the fibers and also preserved the strength (Chen et al, 2020;Mousavipazhouh et al, 2018).…”
Section: Mechanical Properties Of the Fluting Papersmentioning
confidence: 97%
“…Some research in the field of papermaking has shown the compatibility of precipitated calcium carbonate (PCC) with organic compounds [ 5 , 6 , 7 , 8 , 9 ]. The most modifications of precipitated calcium carbonate (PCC) regarding the improvement of its filler properties are those related to the use of bio-additives (starch, alginate, cellulose, and chitosan) which reduce the negative impact of fillers on the paper properties and on the technological process [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%